Overview on Endocrine disruptors in food and their effects on infant's health - Oya Ercan; Gurkan Tarcin (Elsevier, 2022)
Endocrine disruptors (EDs) are natural or synthetic chemicals that cause changes in the body's hormonal and homeostatic systems. Children, especially developing fetuses and infants, are more likely to be affected by these chemicals than adults. Intake through food is one of the primary pathways for EDs to enter the body. While EDs can be found naturally in some foods, synthetic EDs primarily contaminate food, including breast milk and water. Although safe doses have been reported for many EDs, this issue may be controversial because of the low-dose effects and non-monotonic dose responses of EDs. Because of their epigenetic effects, their effects may occur in subsequent generations that are not directly exposed. Some EDs are persistently present in the environment. These chemicals are transported through water and air currents, as well as migratory animals and enter the food chain even if the chemical is banned or not produced in that specific area.In this article, we aim to provide information on EDs by emphasizing those found in food and their effects especially on the health of children including developing fetuses. Some suggestions have also been given to reduce the danger due to EDs.